Localization at large N in Chern–Simons-matter theories*This is a contribution to the review issue 'Localization techniques in quantum field theories' (ed Pestun and Zabzine) which contains 17 chapters available at [001]. (13th October 2017) - Mariño, Marcos
Abstract: We review some exact results for the matrix models appearing in the localization of Chern–Simons-matter theories, focusing on the structure of non-perturbative effects and on the M-theory expansion of ABJM theory. We also summarize some of the results obtained for other Chern–Simons-matter theories, as well as recent applications to topological strings.